2010
DOI: 10.3168/jds.2009-2711
|View full text |Cite
|
Sign up to set email alerts
|

Hot topic: Enhancing omega-3 fatty acids in milk fat of dairy cows by using stearidonic acid-enriched soybean oil from genetically modified soybeans

Abstract: Very long chain n-3 fatty acids such as eicosapentaenoic acid (EPA; 20:5n-3) are important in human cardiac health and the prevention of chronic diseases, but food sources are limited. Stearidonic acid (SDA; 18:4n-3) is an n-3 fatty acid that humans are able to convert to EPA. In utilizing SDA-enhanced soybean oil (SBO) derived from genetically modified soybeans, our objectives were to examine the potential to increase the n-3 fatty acid content of milk fat and to determine the efficiency of SDA uptake from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…Comparable results have been repeatedly reported in the literature (among others, Kälber et al, 2011;Mancilla-Leytón et al, 2013) and may be ascribed to the low and step-decreasing efficiency of ALA metabolism to more unsaturated and long-chain members of the omega-3 FA family (Bernal-Santos et al, 2010). According to the lack of significant difference in LA concentration between OG and GF milk samples, long-chain omega-6 PUFA deriving from LA metabolism were also unaffected by the vegetation type fed by the goats.…”
Section: " "supporting
confidence: 68%
“…Comparable results have been repeatedly reported in the literature (among others, Kälber et al, 2011;Mancilla-Leytón et al, 2013) and may be ascribed to the low and step-decreasing efficiency of ALA metabolism to more unsaturated and long-chain members of the omega-3 FA family (Bernal-Santos et al, 2010). According to the lack of significant difference in LA concentration between OG and GF milk samples, long-chain omega-6 PUFA deriving from LA metabolism were also unaffected by the vegetation type fed by the goats.…”
Section: " "supporting
confidence: 68%
“…Indeed, apparent biohydrogenation of SDA was extensive (Table 2), with more than 98.6% of incubated SDA being hydrogenated, yet it was not affected by its supplementation amounts (P > 0.05). Similarly, Bernal-Santos et al (2010) reported a very low SDA transfer to milk fat when SDA-rich soybean oil was infused in the rumen of multiparous Holstein cows to 2.50 g of SDA/kg of DM. Conversely, another study with lactating cows fed grass silage and cereal-based concentrate (60:40 forage-to-concentrate ratio) supplemented with fish oil was reported to reduce SDA biohydrogenation (58%; Shingfield et al, 2003).…”
Section: Stearidonic Acid Metabolism and Apparent Biohydrogenationmentioning
confidence: 93%
“…Stearidonic acid (SDA; 18:4n-3) is a highly polyunsaturated n-3 fatty acid found in a small number of families of higher plants (mainly Boraginaceae and Primulaceae), with the richest sources known being echium oil (up to 15% SDA; Guil-Guerrero, 2007) and genetically modified oilseeds, such as SDA-enriched soybean oil (Bernal-Santos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Flachowsky et al (2012) reported that changed fatty-acids patterns for soyabeans and derived feed can enrich soyabean oil in stearidonic acid (SDA-oil). It can be transferred into the body fat of lactating cows after duodenal infusion of SDA-soyabean oil (Bernal-Santos et al, 2010), or after feeding ruminal protected SDA-oil to dairy cows (Kitessa and Young, 2011).…”
Section: Discussionmentioning
confidence: 99%